Letermovir prophylaxis in solid organ transplant—Assessing CMV breakthrough and tacrolimus drug interaction. Issue 4 (10th February 2021) - Winstead, Ryan J.; Kumar, Dhiren; Brown, Andrew; Yakubu, Idris; Song, Chelsey; Thacker, Leroy; Gupta, Gaurav
Abstract: Background: Valganciclovir is the preferred drug for cytomegalovirus (CMV) prophylaxis in solid organ transplantation. A limitation to its use is profound myelosuppression. Letermovir is a new agent approved for CMV prophylaxis in hematopoietic stem cell transplantation and is associated with less toxicity. This study aims to assess the effectiveness and safety of letermovir in solid organ transplantation. Methods: A single‐center, matched cohort study was performed on 31 transplant recipients who were converted from valganciclovir to letermovir from November 2017 to June 2020. The primary outcome was the rate of CMV breakthrough infections while on prophylaxis. Secondary outcomes included rate of leukopenia, doses of immunosuppression, rejection, non‐CMV infection, and renal function. Statistical analyses of continuous variables included the student's t‐test, ANOVA test, and Wilcoxon Signed Rank test. Categorical data were analyzed with chi‐square test and Fisher's Exact test. Results: There was no difference in the rate of CMV breakthrough between patients on letermovir (8.7%) and valganciclovir (13.5%), ( P  = .7097). After conversion to letermovir, patients required lower tacrolimus doses at ‐3.34 mg ( SD ‐1.3, P  = .0273), between conversion and day 7. Transplant Infectious Disease The median difference in tacrolimus trough concentrations from conversion to day seven was 9.1 ng/ml [4.9, 16.95] ( P  = .0002). Leukopenia improved by 1.8 109/L [1.08, 4.85] ( P  < .0001). Conclusions: Patients converted from valganciclovir to letermovir did not show an increased rate of CMV breakthrough compared to a historical, matched cohort of patients remaining on valganciclovir. A significant drug interaction was noted with tacrolimus, leading to a recommendation to reduce the dose by 40‐50% upon initiation of letermovir.